PENGARUH MODEL PEMBELAJARAN INKUIRI HIPOTETIK TERHADAP KETERAMPILAN BERPIKIR KRITIS DAN KETERAMPILAN PROSES SAINS SISWA SMP - KUSMIANTI KUSMIANTI (GANEC SWARA, 2018)
The purpose of this research is to analyze: (1) the difference of critical thinking skills (CTS) and scienceprocess skills(SPS) between student’s group who are managed with hypothetical inquiry model andconventional learning model, (2) the difference of critical thinking skills (CTS) between student’s group whoare managed with hypothetical inquiry model and conventional learning model, (3) the difference of scienceprocess skills (SPS) between student’s group who are managed with hypothetical inquiry model andconventional learning model. This research is quasi experiments with post-test only control group designfactorial 2x1. Data of critical think skill are collected by using test and data of science processskillscollected by using test and observation. Data analyzed by using descriptive analyze and one wayMANOVA.It is found: (1) there is significant difference of critical thinking skills (CTS) and science processskills(SPS) between student’s group who are managed with hypothetical inquiry model and conventionallearning model (F=59,161; p<0,05), (2) there is significant difference of critical thinking skills (CTS)between student’s group who are managed with hypothetical inquiry model and conventional learningmodel(F=22,219; p<0,05), (3) there is significant difference of science process skills (SPS) betweenstudent’s group who are managed with hypothetical inquiry model and conventional learning model(F=113.559; p<0,05).